Implementation of Problem Based Learning (PBL) in the introductory business course to improve student activity - Irawati, Winaika; Rakhmawati, Dwi Yuli; Patrikha, Finisica Dwijayati; Rafida, Veni (Technium Social Sciences Journal, 2025)
This study aims to describe the application of problem-based learning in an effort to improve the activeness of Business Education students in introductory business courses. One of the advantages of the problem-based learning method is that it is able to train students in using various concepts, principles and skills that they have learned to solve the problems they are facing. By implementing problem-based learning, it can increase students’ activeness in the problem-solving process because the student’s activeness observed in this study is in the form of the ability to identify, analyze, solve problems, think logically and make decisions correctly and can draw conclusions.This study was conducted in two cycles, focusing on increasing students’ active participation in the learning process. Data collection techniques used questionnaires and observation sheets, while data analysis used qualitative methods. The results of the study showed a significant increase in student learning activity or participation in each cycle, from 55% in cycle 1 to 88% in cycle 2. This increase indicates that PBL is effective in stimulating students to think critically, communicate, and work together in solving problems. The success of this study can be attributed to the ability of lecturers to guide students effectively and create a conducive learning atmosphere. The implication of this study is that the PBL model can be an effective alternative for lecturers in improving the quality of learning and achieving more optimal learning objectives. Keywords: Method, Problem Based Learning, Activeness.